The Influence of Product Innovation and Brand Image on Customer Purchase Decision on Oppo Smartphone Products in South Tangerang City - Yusuf, Ade (Budapest International Research and Critics University, 2021)
This study aims to determine the effect of product innovation and Brand Image on Consumer Purchase Decisions of OPPO Smartphone Products in South Tangerang City. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study that product innovation has a significant effect on purchasing decisions by 42.1%, hypothesis testing obtained t count> t table or (8.274> 1.986). Brand Image has a significant effect on Purchasing Decision by 37.4%, hypothesis testing is obtained t count> t table or (7.488> 1.986). Product innovation and brand image simultaneously have a significant effect on purchasing decisions with the regression equation Y = 10.355 + 0.411X1 + 0.340X2 and the contribution of the effect is 50.4%, the hypothesis test is obtained F count> F table or (47.521> 2.770).